2017
DOI: 10.1093/cid/cix139
|View full text |Cite
|
Sign up to set email alerts
|

A Handshake From Antimicrobial Stewardship Opens Doors for Infectious Disease Consultations

Abstract: Implementation of a unique in-person pediatric antimicrobial stewardship program was associated with a significant increase in infectious disease consultations at a quaternary care children's hospital. This study demonstrates that antimicrobial stewardship programs support, and do not compete with, infectious disease programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…In this study, the annual number of consultations increased rapidly from 211 in 2010 to 1255 in 2016, as the number of fellow physicians increased. Consultation does impact the management of infectious diseases and should have a synergistic effect on antimicrobial use (Butt et al, 2015;Messacar et al, 2017). Although restrictions on physician autonomy were introduced, no backlash from the prescribing physicians was experienced.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the annual number of consultations increased rapidly from 211 in 2010 to 1255 in 2016, as the number of fellow physicians increased. Consultation does impact the management of infectious diseases and should have a synergistic effect on antimicrobial use (Butt et al, 2015;Messacar et al, 2017). Although restrictions on physician autonomy were introduced, no backlash from the prescribing physicians was experienced.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study observed that despite the introduction of an AMS program, there was no reduction in the number of Infectious Diseases consultations, and on the contrary, the authors saw a rise in consultations after AMS implementation. 13 Whether corridor advice or curbside consultation made any impact on this particular question in our survey remains uncertain. Certainly more informal Infectious Diseases consultations have been received on AMS rounds as the consultants are easily accessible on the wards to discuss patients while doing AMS rounds.…”
Section: Discussionmentioning
confidence: 89%
“…26 Direct, face-to-face interactions such as "handshake stewardship" is always favored when possible, because they foster a collaborative relationship between the stewardship team and clinicians, but they can be labor intensive. 27 Although telephone calls or notes in the medical record will never be substitutes for human interactions, they can play an important role in promoting evidence-based antibiotic use and may be more feasible for many programs. Stewardship programs may want to consider prior approval, postprescription review with feedback, or a combination of the 2 approaches to encourage judicious antibiotic use.…”
Section: Prior Approval Versus Postprescription Review With Feedbackmentioning
confidence: 99%